Old-Age Pension and Extended Families: How is Adult Children's Internal Migration Affected? - Xi Chen (Institute for the Study of Labor (IZA), 2016)
This paper makes use of the most recent social pension reform in rural China to examine whether receipt of the pension payment equips adult children of pensioners to migrate. Employing a regression discontinuity (hereafter RD) design to a primary longitudinal survey, this paper overcomes challenges in the literature that households eligible for pension payment might be systematically different from ineligible households and that it is difficult to separate the effect of pension from that of age or cohort heterogeneity. Around the pension eligibility age cut-off, results reveal large and significant increase among adult sons (but not daughters) to migrate out of their home county. Meanwhile, adult children are more likely to migrate out if their parents are healthy. Our Fuzzy RD estimations survive a standard set of key placebo tests and robustness checks.
Keywords: H55; I38; J14; J22; 330; rural pension; RD Design; adult children; migration